Impact of the Gut Microbiome on the Progression of Hepatitis B Virus Related Acute-on-Chronic Liver Failure - Yao, Xuebing; Yu, Haiping; Fan, Guoyin; Xiang, Haihong; Long, Lin; Xu, Huili; Wu, Zhiguo; Chen, Mingfa; Xi, Wenna; Gao, Zhen; Liu, Cuiyun; Gong, Wenlan; et al. (Frontiers in Cellular and Infection Microbiology, 2021)
The relationship between the progression of hepatitis B virus-related acute-on-chronic liver failure (HBV-ACLF) and the gut microbiota is poorly understood, and an HBV-ACLF-related microbiome has yet to be identified. In this study alterations in the fecal microbiome of 91 patients with HBV-ACLF (109 stool samples), including a cohort of 9 patients at different stages of HBV-ACLF, were determined by high-throughput 16S rDNA sequencing. The operational taxonomic units and Shannon indexes indicated that the diversity and abundance of the gut microbiome significantly decreased with the progression of HBV-ACLF (p < 0.05). The relative abundance of the Bacteroidetes phylum in the microbiome was significantly reduced, whereas the abundance of potentially pathogenic bacteria, such as Veilonella, Streptococcus, Enterococcus, and Klebsiella, was highly enriched in the HBV-ACLF group compared with the healthy control group. The abundance of Bacteroidetes was negatively correlated with the level of serum alpha fetoprotein, and the abundance of Veilonella was positively correlated with serum total bilirubin (TBIL). Furthermore, the abundance of Coprococcus was significantly negatively correlated with the level of serum TBIL and the international normalized ratio and positively correlated with prothrombin time activity. Our findings suggest that the gut microbiota plays an important role in the development of HBV-ACLF.